Advancing Antiracism in Literacy Research. (November 2021) - Willis, Arlette Ingram; Smith, Patriann
This invited article is a precursor to the Racial Justice in Literacy Research Report. It is framed around the key concepts of equity, literacy, race, and their intersections in the field of literacy research. The authors make the case that antiracism is the best antidote to a history of unacknowledged racism in the field and in contemporary practice. The authors outline several fundamental principles of antiracism, beginning with working definitions of antiracism, institutional racism, and structural/systemic racism. The authors provide examples of frameworks used to engage antiracism in education broadly and conclude with suggestions for an antiracism framework for literacy research.